2017
DOI: 10.1080/10495398.2017.1304950
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel SNPs ofPPARγSignificantly Affect Weaning Growth Traits of Nanyang Cattle

Abstract: Peroxisome-proliferator-activated receptor gamma (PPARγ) is a key transcription factor that controls adipocyte differentiation and energy in mammals. Therefore, PPARγ is a potential factor influencing animal growth traits. This study primarily evaluates PPARγ as candidate gene for growth traits of cattle and identifies potential molecular marker for cattle breeding. Per previous studies, PPARγ mRNA was mainly expressed at extremely high levels in adipose tissues as shown by quantitative real-time polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Candidate gene is a useful method to investigate the association between phenotypes and genotypes, which is helpful for improving important economical traits in beef cattle [24,25,26]. Recent data have shown that effective molecular markers used in the selection of beef quality traits could bring benefits in the beef industry [27].…”
Section: Discussionmentioning
confidence: 99%
“…Candidate gene is a useful method to investigate the association between phenotypes and genotypes, which is helpful for improving important economical traits in beef cattle [24,25,26]. Recent data have shown that effective molecular markers used in the selection of beef quality traits could bring benefits in the beef industry [27].…”
Section: Discussionmentioning
confidence: 99%
“…Results were presented as means ±SE. Other details can be found in a previous study (Huang et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Samples used in this study were shown in a previous study (Huang et al, 2017). Briefly, seven tissues were collected at the slaughter house for reverse transcription polymerase chain reaction (RT-PCR), including heart, liver, spleen, lung, kidney, muscle, and adipose of three Jiaxian cattle (bullock, 30 months).…”
Section: Samplesmentioning
confidence: 99%
See 2 more Smart Citations